2016
DOI: 10.1177/2158244016661748
|View full text |Cite
|
Sign up to set email alerts
|

A Reliability Generalization of the Suinn-Lew Asian Self-Identity Acculturation Scale

Abstract: A reliability generalization was conducted on studies that reported use of the Suinn-Lew Asian Self-Identity Acculturation Scale (SL-ASIA), published between 1987 and 2013. For inclusion in this meta-analysis, each study had to have reported a Cronbach's alpha reliability coefficient for its sample. Data from 83 Cronbach's alpha coefficients representing 12,992 participants were analyzed; only 67 out of 193 published studies (43.52%) reported reliability scores for their sample. The reliability scores produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Psychometric properties of the original SL-ASIA are addressed in a wide range of literature. The legibility and writing quality, satisfactory test-retest reliability over a short time, and adequate internal consistency of the scale are confirmed in numerous studies (2,13,16). A metaanalysis review of published studies from 1987 to 2013 reporting the application of any version of the SL-ASIA showed that all reliability scores of this instrument range acceptable to excellent (2).…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Psychometric properties of the original SL-ASIA are addressed in a wide range of literature. The legibility and writing quality, satisfactory test-retest reliability over a short time, and adequate internal consistency of the scale are confirmed in numerous studies (2,13,16). A metaanalysis review of published studies from 1987 to 2013 reporting the application of any version of the SL-ASIA showed that all reliability scores of this instrument range acceptable to excellent (2).…”
Section: Introductionmentioning
confidence: 79%
“…Significant population movement in the 21st century has led to an expanded interest in acculturation research and the demand for culturally and psychometrically sound measures (1). Acculturation happens when people from diverse cultural backgrounds come into continuous first-hand contact, and is defined as the process by which individuals adopt the attitudes, values, customs, beliefs, and behaviors of another culture (1,2). The concept of acculturation was originally proposed by Redfield, Linton, and Herskovits, and through the years, a variety of approaches are suggested to conceptualize and measure acculturation (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current literature treating this process as unidimensional suggests that acculturation may be measured on a scale from low acculturation to high acculturation, broadly allowing for three outcomes: Assimilation (high acculturation, in which a person mostly associates with Western culture) Separation (low acculturation, in which a person mostly associates with ethnic culture), and Integration (neither high nor low acculturation, in which a person associates equally with Western and ethnic culture). To determine these outcomes, acculturation was A meta-analysis review of studies published between 1987 and 2013 in which any version of the SL-ASIA scale was applied found that all reliability scores of the instrument ranged from acceptable to excellent, with Cronbach's alpha scores ranging from .62 to .96 with an average of .91 (SD=.07) (Phillips, King, Kivisalu, & O'Toole, 2016). Suinn, Ahoona, & Khoo's (1992) study regarding Asian migrants found significant correlation between acculturation scores using the SL-ASIA scale and demographic variables reflecting levels of Asian-American identity, (2020) found the reliability of the orthogonal SL-ASIA scale to improve from .44 to .67, which was determined to be satisfactory.…”
Section: Acculturationmentioning
confidence: 99%